Transformation of impurity-defect centers in single crystals CdTe:Cl under the influence of microwaves - Vakhnyak, N.D.; Lotsko, O.P.; Budzulyak, S.I.; Demchyna, L.A.; Korbutyak, D.V.; Konakova, R.V.; Red’ko, R.A.; Okhrimenko, O.B.; Berezovska, N.I. (Semiconductor Physics Quantum Electronics & Optoelectronics, 2017)
Performed in this work is the research of the influence of microwave irradiation (2.45 GHz, 24 GHz) on the spectra of low-temperature (T = 2 K) photoluminescence (PL) in single crystals CdTe:Cl. The transformation of impurity-defect centers in CdTe:Cl, responsible for PL within the spectral range 1.3 to 1.5 eV under microwave irradiation, was analyzed. The parameter of electron-phonon interaction (Huang–Rhys factor) for the donor-acceptor PL band, which depends on the time of microwave irradiation, has been calculated.